PENYULUHAN PENGELOLAAN SAMPAH PADA SISWA SEKOLAH DASAR NEGERI 008 SALO - Ade Dita Puteri; Devina Yuristin (Universitas Pahlawan Tuanku Tambusai, 2022)
The waste problem is one of the important problems faced by Indonesia. However, people's understanding of the importance of waste management is still not ideal. The importance of education regarding waste management needs to be done early on so that the harmful effects of waste can be reduced. For this reason, the purpose of this community service activity is to create awareness and increase children's basic school knowledge about the importance of sorting waste according to its type. Method This community service activity is in the form of counseling and hands-on practice, where the children of SD Negeri 008 Salo are directly taught to sort waste and put the waste in the organic or non-organic bins that have been provided. The result of this community service is increased knowledge about waste management and the application of basic schooling by children starting from their own environment and daily life. Suggestions for further community service activities can be directed to the practice of how to process and recycle organic and non-organic waste. Keywords: school children, counseling, waste management